Effect of different nutritional management on yield and quality of tomato fruits - Terry Alfonso, Elein (2018)
The conversion of high-input agriculture to an agro-ecological approach bring harmony to the environment reducing degraded Agroecosystems. The objective of this study was to evaluate the effect of different nutritional management on yield and internal and external quality of tomato fruits as an alternative to the reduction of mineral fertilizers. The research was carried out at the National Institute of Agricultural Sciences (INCA) in Cuba, from September 15 to November 30, 2016. A randomized block design with four replications was used to study four treatments: Absolute control (without mineral fertilizer and bioproducts), Partial ecological nutrition (50 % of mineral fertilizer + bioproducts: mycorrhiza and biostimulant), Organic nutrition (organic fertilizer + bioproducts: mycorrhiza and biostimulant), and Conventional nutrition (NPK mineral fertilizer only). Evaluations regarding agricultural yield and its components, bromatological quality of fruits (Brix, acidity, vitamin C content, and nitrates) and postharvest indices (fruit firmness and diameter of endocarp and mesocarp) were performed. Agricultural yield (25.31 t/ha) and the internal quality of fruits (5.23 °Brix; 11.75 SST; 73.29 nitrates; 18.54 vitamin C, and 4.45 dry matter) applying the treatment where 50% of mineral fertilization was dispensed and complemented by bioproducts did not show significant differences with NPK treatment. Regarding the organic variant, the result in agricultural yield was lower (19.42 t/ha), in comparison with control and the ecological variant. Therefore, it is suggested further evaluation of the effect of the reduction of mineral fertilization on tomato crop and its combination with bioproducts.